Dehydration in the tropical tropopause layer: A case study for model evaluation using aircraft observations. Issue 9 (13th May 2014) - Ueyama, Rei; Jensen, Eric J.; Pfister, Leonhard; Diskin, Glenn S.; Bui, T. P.; Dean‐Day, Jonathan M.
Abstract The dynamical and microphysical processes that influence water vapor concentrations in the tropical tropopause layer (TTL) are investigated in simulations of ice clouds along backward trajectories of air parcels sampled during three flights of the Airborne Tropical Tropopause Experiment over the central to eastern tropical Pacific in boreal fall 2011. ERA‐Interim reanalysis temperatures interpolated onto the flight tracks have a negligible (−0.09 K) cold bias compared to aircraft measurements of tropical cold point temperature thus permitting case study simulations of TTL dehydration. When the effects of subgrid‐scale waves, cloud microphysical processes, and convection are considered, the simulated water vapor mixing ratios on the final day of 40 day backward trajectories exhibit a mean profile that is within 20–30% of the mean of the aircraft measurements collected during vertical profiling maneuvers between the 350 and 410 K potential temperature levels. Averaged over the three flights, temperature variability driven by subgrid‐scale waves dehydrated the 360–390 K layer by approximately −0.5 ppmv, whereas including homogeneous freezing of aqueous aerosols and subsequent sublimation and rehydration of ice crystals increased water vapor below the 380 K level by about +1 ppmv. The predominant impact of convection was to moisten the TTL, resulting in an average enhancement below the 370 K level by +1 to 5 ppmv. Accurate (to within 0.5–1 ppmv) predictions of TTL water vapor using trajectory models require proper representations of waves, in situ ice cloud formation, and convective influence, which together determine the saturation history of air parcels.